2009
DOI: 10.1097/ta.0b013e318190392b
|View full text |Cite
|
Sign up to set email alerts
|

What's the Incidence of Delayed Splenic Bleeding in Children After Blunt Trauma? An Institutional Experience and Review of the Literature

Abstract: DSB is exceedingly rare. Our institutional incidence is 1 of 303 (0.33%). The number and quality of reported cases is insufficient to draw conclusions on predisposing factors for DSB, however, most cases occur in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Given the success of NOM for blunt splenic trauma and the absence of routine follow-up imaging in most institutions, it is likely that many posttraumatic SAP still go undetected and resolve spontaneously without any long-term sequalae [4,9,13,28]. Delayed splenic rupture is thought to be very rare (b1%) in the pediatric population, with some larger series reporting no ruptures [27][28][29]. Adult data have demonstrated that both contrast blush and SAP predict delayed splenic bleeding and the failure of NOM [6,8,10].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Given the success of NOM for blunt splenic trauma and the absence of routine follow-up imaging in most institutions, it is likely that many posttraumatic SAP still go undetected and resolve spontaneously without any long-term sequalae [4,9,13,28]. Delayed splenic rupture is thought to be very rare (b1%) in the pediatric population, with some larger series reporting no ruptures [27][28][29]. Adult data have demonstrated that both contrast blush and SAP predict delayed splenic bleeding and the failure of NOM [6,8,10].…”
Section: Discussionmentioning
confidence: 95%
“…The fear of delayed splenic rupture and other late complications of posttraumatic SAP, such as AVF formation, were often cited as the reason for intervention in otherwise stable children [3,7,16,17,26]. Interestingly, Davies et al [27] reported a case of a boy, aged 15 years, who died of delayed splenic bleeding 23 days after his initial injury. This patient had follow-up imaging before hospital discharge that had ruled out SAP, raising the possibility of other mechanisms of delayed splenic rupture in children [27].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Crawford et al 18 reported a case of a 22-year-old man who experienced delayed rupture of his spleen 22 days after injury, and Fernandes 19 reported a case of a 34-year-old man who had delayed rupture about 2 years after initial splenic injury. In addition, Davies et al 20 reported that a 15-year-old boy who experienced a Grade IV injury and was discharged after 5 days with no SPA detected died from delayed splenic bleeding 18 days later. In the present study, all patients were carefully followed up with repeat enhanced CT, and no patient experienced delayed rupture during the observation period in the trauma centers studied.…”
Section: Discussionmentioning
confidence: 97%
“…This led to the first case–control study on operative versus non‐operative management by Upadhyaya and Simpson34 in 1968, which suggested that isolated splenic injuries could safely be treated without surgery in children. Paediatric surgeons led the way during the following decades, and non‐operative management is now reported to be successful in more than 90 per cent of children with isolated blunt splenic injuries22, 35, 36.…”
Section: Rationale For Non‐operative Managementmentioning
confidence: 99%